Jeremiah and the Balag-Lament? Jeremiah 8:18-23 Reconsidered - Baker, Robin ca. 20./21. Jh. (Journal of Biblical literature, 2019)
Commentaries on Jer 8:18-23 generally recognize that this celebrated passage represents a cohesive lament over the destruction facing Judah. Exegesis of the passage has been impaired, however, by the opacity of the lament's opening verse and particularly of its initial word, a notorious crux interpretum. In this article, I analyze the word in light of the Akkadian noun balaggu. I offer a new reading of the verse and explore the Mesopotamian cultural influences that appear to have been at work in the composition of the lament.